Study on the Identification of Radix Bupleuri from Its Unofficial Varieties Based on Discrete Wavelet Transformation Feature Extraction of ATR-FTIR Spectroscopy Combined with Probability Neural Network - Wenying Jin; Chayan Wan; Cungui Cheng (International Journal of Analytical Chemistry)
The attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR) was employed to acquire the infrared spectra of Radix Bupleuri and its unofficial varieties: the root of Bupleurum smithii Wolff and the root of Bupleurum bicaule Helm. The infrared spectra and spectra of Fourier self-deconvolution (FSD), discrete wavelet transform (DWT), and probability neural network (PNN) of these species were analyzed. By the method of FSD, there were conspicuous differences of the infrared absorption peak intensity of different types between Radix Bupleuri and its unofficial varieties. But it is hard to tell the differences between the root of Bupleurum smithii Wolff and the root of Bupleurum bicaule. The differences could be shown more clearly when the DWT was used. The research result shows that by the DWT technology it is easier to identify Radix Bupleuri from its unofficial varieties the root of Bupleurum smithii Wolff and the root of Bupleurum bicaule.